Assessment of the impact of solvent/detergent treatment on the quality and potency of a whole IgG equine antivenom - Segura Ruiz, Álvaro (2009)
We have evaluated for the first time the impact of a solvent/detergent (S/D) treatment on the quality and in vivo neutralization potency of horse-derived whole IgG antivenom used in the treatment of viperid snake bite envenoming in Central America. The S/D treatment by 1% tri (n-butyl) phosphate (TnBP) – 1% Triton X-45 at 22–25 °C was applied either on starting plasma or on purified immunoglobulins. The S/D agents were removed from both fractions by extractions with oil. S/D-treated plasma was subjected to caprylic acid precipitation to purify the immunoglobulins. Products were formulated, sterile-filtered, and filled into 10-mL vials, stored at 5 ± 3 °C, and subjected to routine quality controls, SDS-PAGE, determination of anti-Bothrops asper venom antibody titre by ELISA, in vivo B. asper venom-neutralization potency tests, and safety test, comparatively with an antivenom manufactured by caprylic acid fractionation without S/D treatment. Results indicate that these conditions of S/D treatment on purified immunoglobulin yielded an antivenom of high turbidity that induced weight loss in animals. In contrast, antivenom fractionated from the S/D-treated plasma had physico-chemical and biological characteristics indistinguishable from those of the non-S/D-treated antivenom. S/D treatment of horse plasma may be considered to increase the viral safety of antivenoms.